Adaptive introgression: how polyploidy reshapes gene flow landscapes. Issue 2 (19th February 2021) - Schmickl, Roswitha; Yant, Levi
Summary: Rare yet accumulating evidence in both plants and animals shows that whole genome duplication (WGD, leading to polyploidy) can break down reproductive barriers, facilitating gene flow between otherwise isolated species. Recent population genomic studies in wild, outcrossing Arabidopsis arenosa and Arabidopsis lyrata indicate that this WGD‐potentiated gene flow can be adaptive and highly specific in response to particular environmental and intracellular challenges. The mechanistic basis of WGD‐mediated easing of species barrier strength seems to primarily lie in the relative dosage of each parental genome in the endosperm. While generalisations about polyploids can be fraught, this evidence indicates that the breakdown of these barriers, combined with diploid to polyploid gene flow and gene flow between polyploids, allows some polyploids to act as adaptable 'allelic sponges', enjoying increased potential to respond to challenging environments.